Low resistivity and permeability in actively deforming shear zones on the San Andreas Fault at SAFOD. Issue 12 (21st December 2015) - Morrow, C.; Lockner, D. A.; Hickman, S.
Abstract: The San Andreas Fault Observatory at Depth (SAFOD) scientific drill hole near Parkfield, California, crosses the San Andreas Fault at a depth of 2.7 km. Downhole measurements and analysis of core retrieved from Phase 3 drilling reveal two narrow, actively deforming zones of smectite‐clay gouge within a roughly 200 m wide fault damage zone of sandstones, siltstones, and mudstones. Here we report electrical resistivity and permeability measurements on core samples from all of these structural units at effective confining pressures up to 120 MPa. Electrical resistivity ( 10 Ω‐m) and permeability (10 −21 to 10 −22 m 2 ) in the actively deforming zones were 1 to 2 orders of magnitude lower than the surrounding damage zone material, consistent with broader‐scale observations from the downhole resistivity and seismic velocity logs. The higher porosity of the clay gouge, 2 to 8 times greater than that in the damage zone rocks, along with surface conduction were the principal factors contributing to the observed low resistivities. The high percentage of fine‐grained clay in the deforming zones also greatly reduced permeability to values low enough to create a barrier to fluid flow across the fault. Together, resistivity and permeability data can be used to assess the hydrogeologic characteristics of the fault, key to understanding fault structure and strength. The low resistivities and strength measurements of the SAFOD core are consistent with observations of low resistivity clays that are often found in the principal slip zones of other active faults making resistivity logs a valuable tool for identifying these zones. Key Points: Electrical resistivity and permeability are reduced in the deforming zones at SAFOD Deforming zone permeability is low enough to create a barrier to fluid flow across the fault